Students Perception of Diglossia Phenomenon in Classroom - Artika, Chessy; Safitri, Amalia; Norjannah, Norjannah; Nor Azhar, Nurul Fathihah; Banseng, Saripah (Peneliti.net, 2024)
The occurrence of diglossia is seen in several contexts and settings, including both official and informal domains. This study's primary objective is to investigate students' language preferences, motivations, and language attitudes. Data were collected from undergraduate English students at the Muhammadiyah University of Banjarmasin via questionnaire in Google Form. The study used a descriptive quantitative methodology. The present research used a descriptive test analysis approach using the SPSS version 25 software for Windows. According to the results on language selection, the association between high variation (H) and low variation (L) may be diglossic. Regarding linguistic attitudes, most respondents exhibit a favourable disposition towards a wide variety instead of low variation across all dimensions. This inclination may be attributed to their academic specialisation. Nevertheless, a significant proportion of participants believed that the Low variation had supplanted the High variety as the predominant linguistic form used by the Indonesian population. Therefore, the diglossic link between the High and Low types will persist in Indonesia. The study results provide insights into the diglossic condition of diglossia in a multilingual society and provide a reflection of the perspectives held by young people in Indonesia about the two distinct kinds present within their communities.